2021
DOI: 10.3390/app11209566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Different Spatial Interpolation Methods Applied to Monthly Rainfall as Support for Landscape Management

Abstract: Landscape management requires spatially interpolated data, whose outcomes are strictly related to models and geostatistical parameters adopted. This paper aimed to implement and compare different spatial interpolation algorithms, both geostatistical and deterministic, of rainfall data in New Zealand. The spatial interpolation techniques used to produce finer-scale monthly rainfall maps were inverse distance weighting (IDW), ordinary kriging (OK), kriging with external drift (KED), and ordinary cokriging (COK).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Omitting these activities in the future could result in severe damage to the soil structure, rendering it unsuitable for agricultural purposes and diminishing the economic benefits derived from agricultural activities. Therefore, concerted efforts are needed to safeguard Mexico's agricultural resources and promote sustainable land management practices for the benefit of present and future generations [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Omitting these activities in the future could result in severe damage to the soil structure, rendering it unsuitable for agricultural purposes and diminishing the economic benefits derived from agricultural activities. Therefore, concerted efforts are needed to safeguard Mexico's agricultural resources and promote sustainable land management practices for the benefit of present and future generations [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Spatial interpolation assumes that the attributes of the data are continuous in space and exhibit spatial relationships. Several spatial interpolation methods have been widely employed by researchers, including Multiple Linear Regression, Local Polynomial, Inverse Distance Weighted, Ordinary Kriging, Simple Kriging, Universal Kriging, and Empirical Bayesian Kriging (EBK) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the geostatistical interpolation methods employed were Ordinary Kriging, Simple Kriging, Empirical Bayesian Kriging, and Universal Kriging. Caloiero et al [2] employed the Inverse Distance Weighted, Ordinary Kriging, the Kriging with External Drift, and Ordinary Cokriging interpolation methods to interpolate monthly rainfall data in New Zealand. They conducted a comparative analysis of these four interpolation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Xing [25] compared kernel interpolation with barrier (KIB), diffusion interpolation with barrier (DIB), IDW, RBF, OK, and EBK methods using precipitation data from different time series in Chongqing (China), and they found that the KIB method provided the highest accuracy. Caloiero et al [26] compared the IDW, OK, KED, and OCoK methods using monthly precipitation data in New Zealand and found OCoK to be the optimal method. Fung et al [27] compared the IDW, OK, multi-scale geographical weighted regression (MGWR), and geographical weighted regression (GWR) methods using precipitation data from different periods in Peninsular Malaysia and found MGWR to be the best-performing model.…”
Section: Introductionmentioning
confidence: 99%